PDA@Ti3C2Tx as a novel carrier for pesticide delivery and its application in plant protection: NIR‐responsive controlled release and sustained antipest activity. Issue 11 (19th July 2021) - Wu, Wenneng; Wan, Minghui; Fei, Qiang; Tian, Yu; Song, Saijie; Shen, He; Shen, Jian
Abstract: BACKGROUND: Stimuli‐responsive pesticide controlled release system provides a new strategy for the development of high‐efficiency pesticides formulation. RESULTS: In this article, we report a novel polydopamine surface modified MXene‐Ti3 C2 T x nanocarrier for pesticide delivery and plant protection. Polydopamine modified Ti3 C2 T x (PDA@Ti3 C2 T x ) nanocarrier was prepared by biomimetic self‐polymerization of dopamine on the surface of Ti3 C2 T x . A typical pesticide, emamectin benzoate (EB), was loaded on PDA@Ti3 C2 T x through physisorption process, with a high pesticide loading rate of 45.37%. PDA@Ti3 C2 T x exhibited excellent photothermal conversion effect ( η = 34.5%). Under the irradiation of near‐infrared (NIR) laser, EB would sustained release from PDA@Ti3 C2 T x nanocarrier to surrounding medium. Compared with free EB, EB@PDA@Ti3 C2 T x exhibited prolonged persistence period, which can keep antipest activity at 14 days post spraying. In addition, PDA@Ti3 C2 T x nanocarrier and EB@PDA@Ti3 C2 T x nanoformulation are of good safety, showing no side effect to the seed germination and seedling growth. CONCLUSION: This research developed a novel nanocarrier for water‐insoluble pesticide delivery, realizing NIR‐responsive controlled release and sustained antipest activity. Abstract : Synthesis of EB@PDA@Ti3 C2 T x nanoformulation and its application for near‐infrared (NIR)‐responsive pesticide release and sustained pest control. © 2021 Society of Chemical Industry.